Family Functioning and Quality of Life among Families in Eating Disorders: A Comparison with Substance‐related Disorders and Healthy Controls. (24th February 2016) - Anastasiadou, Dimitra; Sepulveda, Ana R.; Sánchez, Julio César; Parks, Melissa; Álvarez, Tamara; Graell, Montserrat
Abstract: The aim of this study was to compare the family functioning of Spanish parents of patients with an eating disorder (ED) with that of carers of patients with substance‐related disorders (SRDs) and families of healthy controls (HC). This cross‐sectional study included 48 mothers and 45 fathers of 48 adolescent patients with an ED, 47 mothers and 37 fathers of 47 patients with an SRD and 66 mothers and 50 fathers of 68 HCs. Families of ED patients reported lower levels of criticism, symptom accommodation and negative caregiving experience than families of SRD patients. However, relatives of both ED and SRD patients reported similar levels of quality of life related to their mental health. Furthermore, families of HCs generally exhibited better scores on all scales assessing their caregiving experiences. Regarding gender differences, there was a tendency in mothers, primarily those from the ED group, to report more adverse experiences as caregivers compared with fathers. Symptoms characteristic to each disorder may be associated with differential patterns of family functioning and may require specifically tailored family interventions. Early family intervention in adolescence is crucial, as relatives' quality of life does not seem to have been badly affected at this point in the course of the illness. Copyright © 2016 John Wiley & Sons, Ltd and Eating Disorders Association.